Leukemia Stem Cell-Released Microvesicles Promote the Survival and Migration of Myeloid Leukemia Cells and These Effects Can Be Inhibited by MicroRNA34a Overexpression - Yue Wang; Qian Cheng; Jing Liu; Min Dong (Stem Cells International)
Leukemia stem cells (LSCs) play the major role in relapse of acute myeloid leukemia (AML). Recent evidence indicates that microvesicles (MVs) released from cancer stem cells can promote tumor growth and invasion. In this study, we investigated whether LSCs-released MVs (LMVs) can regulate the malignance of AML cells and whether overexpression of tumor suppressive microRNA (miR), miR34a, is able to interrupt this process. LSCs were transfected with miRNA control (miRCtrl) or miR34a mimic for producing LMVs, respectively, defined as LMVsmiRCtrl and LMVsmiR34a. The effect of miR34a transfection on LSC proliferation and the effects of LMVsmiRCtrl or LMVsmiR34a on the proliferation, migration, and apoptosis of AML cells (after LSC depletion) were determined. The levels of miR34a targets, caspase-3 and T cell immunoglobulin mucin-3 (Tim-3), were analyzed. Results showed that (1) LMVsmiRCtrl promoted proliferation and migration and inhibited apoptosis of AML cells, which were associated with miR34a deficit; (2) transfection of miR34a mimic inhibited LSC proliferation and increased miR34a level in LMVsmiR34a; (3) LMVsmiR34a produced opposite effects as compared with LMVsmiRCtrl, which were associated with the changes of caspase-3 and Tim-3 levels. In summary, LMVs support AML cell malignance and modulating miR34a could offer a new approach for the management of AML.